Influences of roughness and filling degree on the shear strength and damage evolution characteristics of cement-filled joints. - Zhilin Shu; Yang Liu; Yicheng Ye; Weiqi Wang; Binyu Luo; Jinpeng Jia (PLoS ONE)
The shear resistance of filling joints is an important factor affecting the stability of rock joints. Pressure-shear tests of cement-filled joints were carried out. Combined with the acoustic emission (AE) technique, the effects of normal stress, roughness and filling degree on the shear strength, damage morphology and damage evolution of cement-filled joints were investigated. The results show that with the increase of roughness, the failure mode is more complicated. When the roughness is low, only the bonding surface of the interface between the filler and the joint surface is damaged, and the filling degree has a weak effect on the failure mode. When the roughness is high, with the increase of normal stress and filling degree, the failure of the filled joint is from the joint failure of the bonding surface and the filling material to the serious failure of the bonding surface, the filling material and the joint. The peak shear strength of filled joints is positively correlated with roughness and negatively correlated with filling degree. With the increase of filling degree, the influence of roughness will be weakened by filling material, and the normal stress will amplify the effect of roughness. The evolution characteristics of AE show that the damage degree of filled joints is positively correlated with normal stress and roughness, and negatively correlated with filling degree. The joint surface is damaged locally at first, then failure near the main raised body of the joint, and finally spreads to the whole joint surface.